The effects of using aliovalent doping in cerium bromide scintillation crystals - Harrison, Mark J. (Kansas State University, 2009)
Strengthening the crystal lattice of lanthanide halides, which are brittle, anisotropic, ionic crystals may increase the availability and ruggedness of these scintillators for room-temperature γ-ray spectroscopy applications. Eight dopants for CeBr[subscript]3, including CaBr[subscript]2, SrBr[subscript]2, BaBr[subscript]2, ZrBr[subscript]4, HfBr[subscript]4, ZnBr[subscript]2, CdBr[subscript]2, and PbBr[subscript]2, were explored at two different doping levels, 500ppm and 1000ppm, in an effort to identify potential aliovalent strengthening agents which do not adversely affect scintillation performance. All dopants and doping levels exhibited improved ingot yields over the undoped case, indicating an improvement in the ease of crystal growth. Scintillation performance was gauged using four key metrics. Scintillation emission spectra or, rather, radioluminescence spectra were recorded using x-ray irradiation. Total light yield was estimated through pulse height comparison with bismuth germanate (BGO) scintillators. Scintillation kinetics were checked by measuring single interaction pulses directly output by a fast response PMT. Finally, light yield proportionality was measured using a Compton coincidence system. Samples from each ingot were harvested to benchmark their performance with the four metrics. Of the eight dopants explored, only BaBr[subscript]2 and PbBr[subscript]2 clearly altered scintillation spectral emission characteristics significantly. The remaining dopants, CaBr[subscript]2, SrBr[subscript]2, ZrBr[subscript]4, HfBr[subscript]4, CdBr[subscript]2 and ZnBr[subscript]2, altered scintillation performance to a lesser degree. No dopant appeared to affect light yield proportionality, nor did any drastically alter the light decay characteristics of CeBr[subscript]3. HfBr[subscript]4 and ZnBr[subscript]2-doped CeBr[subscript]3 exhibited the highest light yields, significantly higher than the undoped CeBr[subscript]3 samples tested. Finally, aliovalent doping appeared to greatly improve CeBr[subscript]3 ingot yields, regardless of the dopant, thus it is a promising method for improving crystal strength while not deleteriously affecting scintillation performance. HfBr[subscript]4 and ZnBr[subscript]2 both demonstrated high performance without any noticeable negative side-effects and are prime candidates for future study.
Keywords: Radiation detection; Scintillators; Solid solution strengthening; Aliovalent doping; Engineering, Materials Science (0794); Engineering, Nuclear (0552)